Knowledge, attitude and practice of female genital mutilations among males and females attending out patients and mch clinic of elder district rural Hospital Galgadud Somalia - A.S Shamsul,; S.A Abdi Nur,; I Halim,; M.A Rahmah, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2008)
Background : Somalia is a country that still practices Female Genital Mutilation (FGM). Female genital mutilation (FGM) constitutes all procedures, which involve partial or total removal of the external female genitalia or other injury to the female genital organs whether for cultural or any other non-therapeutic reasons. Methodology : A cross-sectional community based study was conducted among males and females above 18 years of age attending the Out Patient Clinic and Mother & Child Clinic of Elder District, Rural Hospital Galgadud Region, Somalia in June 2006 using a structured questionnaire to access the respondents’ knowledge, attitude and practice. Results : Four hundred respondents were interviewed and male respondents were noted to be more knowledgeable than their female counterparts (p 0.004) and so does respondents with formal education (p <0.001) and had occupation (p <0.001). Majority of the female respondents (97.1%) favors the practices of FGM and reasons such as to protect virginity (p <0.001), increase marital opportunity (p <0.001) and religious recommendations (p <0.001) were noted to be the important factors in the continuation of FGM. All of the female respondents have had some form of FGM, giving the prevalence rate of 100% with 64.1% underwent the procedure at between the age of 5-10 years old and the commonest form of FGM were infibulations. Mother (69.4%) was the important decision maker for these women. Conclusion : Aggressive education programme should be introduced targeting the women in this community. They should be well informed on the complication of FGM and its health effects. Providing clinics will help to alleviate some of the complications related to FGM. Law on protecting women from these practices should be introduced and enforced.